DAMPAK PERUBAHAN INDIKATOR MONETER TERHADAP KINERJA EKSPOR DI INDONESIA - Anggraeni, Sandra Yulia; Prakoso, Jalu Aji (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
The economic openness of a country is one of the indicators of a highly competitive country. The benefit of the open economy is international trade. This is done to increase state income which can provide community welfare. Changes in the international trade balance affect monetary indicators. International trade consists of export and import activities. The purpose of this study is to analyze the impact of changes in monetary indicators consisting of exchange rates, interest rates, and inflation on export performance in Indonesia from January 2017 to December 2021. The data sources used are from the Central Statistics Agency and Bank Indonesia. This study uses time series secondary data. The analytical method used is the Vector Error Correction Model with the help of EViews 10. There are monetary indicators studied that affect export performance and some do not affect export performance. The exchange rate is proven to have a major influence on and contribute to export performance. The findings of this study show that Indonesia needs to strengthen the rupiah exchange rate.